ANALISIS AKTIVITAS DAKWAH PEMAIN SEPAK BOLA MUSLIM DI MEDIA SOSIAL MOHAMED SALAH HAMED MAHROUS GHALY: ANALYSIS OF MUSLIM FOOTBALL PLAYER'S DA'WAH ACTIVITY ON SOCIAL MEDIA MOHAMED SALAH HAMED MAHROUS GHALY - Ulum, Mohammad Bahrul; Farhan, Farhan; Solihin, Mochammad Alih (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
This article discusses the relationship between da'wah and football, where a Muslim player should be an example (dakwah bil hal) for others. The phenomenon of Muslim footballers in Europe is increasing every year, such as the presence of Mohamed Salah at the Liverpool club in England since July 1 2017, has changed the mindset of non-Muslims in the English league. That Muslim football players have friendly personalities, are not grumpy and also obey the rules that apply both in terms of religion and the rules of the team. Mohamed Salah is the first Egyptian player to join Liverpool, and has never received a red card from a referee to date. What is Mohamed Salah's activity like as a Muslim footballer in the perspective of da'wah bi al-hal? Through descriptive analysis based on cyber media theory on Instagram, Twitter and Youtube social media accounts, which are relevant. The results of the study state that (1) Mohamed Salah's example as a winger is an example for other players to minimize violations and not swear at the opposing team; carry out fasting orders (mandatory) in training and or matches; prostration celebration of gratitude to Allah SWT.; istikamah in the five daily prayers. (2) activities outside the competition include; social service; donations for orphans; defend women; Property Waqf for the Animal Charity Agency (Qurban) of the country of origin; even (3) some of the fans of the club or supporters of Mohamed Salah converted to Islam (converts).